EXOGENOUS MELATONIN ENHANCES CARCASS TRAITS, LITTER CONDITION, AND WELL-BEING OF BROILERS EXPOSED TO HEAT STRESS - Mohammad A. Elsagheer, Mohammed Khalil Ibrahim Al-Saeedi, Hashim Hadi Al-Jebory , Rasha Fajer Al-Jebory, Mohamed R. Eletmany (Chelonian Research Foundation, 2024)
One of the main goals of producing broilers successfully is to maintain dry litter. Exposure to heat stress may be affected carcass traits and litter condition in poultry houses. This study was conducted to evaluate the using exogenous melatonin for elevate the negative effects of heat stress on carcass traits and litter for broiler chickens (Ross 308). 400-one day old broiler chicks were randomly split into five equal groups with four replicates, each with 20 chicks. The first group (C) fed on basal diet without melatonin and served as control. While the second (M1) and third (M2) groups received 10 and 20mg of melatonin / kg diet, respectively. And the 4th and 5th received 10 and 20mg of melatonin in drinking water / Liter, respectively. All birds were subjected to heat stress during the experimental period (1-35 d). Results indicated that carcass yield, breast, thigh and back percentages were significantly (P<0.05) increased for birds received melatonin hormone compared with control. Feces weight was significantly (P<0.05) decreased in birds received melatonin compared to the control group at the 2nd, 4th and 5th weeks of age. Data showed that using of melatonin significantly (P<0.05) improved litter condition (moisture, pH and bacterial count) at heat stress. Also, adding melatonin significantly (P<0.05) improved feather hygiene and decreased footpad dermatitis%. Finally, we can conclude that administration melatonin in diet or drinking water for heat-stressed broilers at levels 10 or 20mg significantly improved carcass traits, litter condition with beneficial effects on well-being of birds.